PERAN MYANMAR MENANGGULANGI PENYELUNDUPAN DAN PENYALAHGUNAAN NARKOBA DALAM MENDUKUNG PENCAPAIAN DRUG-FREE ASEAN 2015 - Eko Bagus Sholihin (HI 16 UMY 068, 2016)
*68 This paper describes drug issues to support achievement Drug-Free ASEAN 2015 programme. Myanmar is the biggest producer of drugs in Southeast Asia, therefore this country has an important role to support achievement of the programme. The government such as domestic policies that include 15 Years Drug Control Plan Programme, Law enforcement, and the Role of Anti-drug Agency (Central Committe of Drug Abuse Control), Foreign Policy that include International Cooperation to against drug abuse and trade, and the last working group with neighbour countries.s Keywords: Role, Myanmar, Drugs, Drug-Free ASEAN 2015